Islamic Perspective and Socio-Cultural Aspects of Pre-Marital Medical Test in Sokoto Metropolis - Aliyu Barmo, Shafa'atu; Yahaya, Atiku Garba (ASANKA : Journal of Social Science and Education, 2024)
The foundation of an egalitarian society is rooted in the family system, and a healthy marital atmosphere is needed to achieve the objective of marriage. Pre-marital medical test plays a vital role that cannot be overemphasized, particularly in limiting the spread of some infectious diseases, such as sickle cell, HIV, thalassemia, etc. However, the fact that some resistance was relatively recorded on the pre-marital medical tests among people in the Sokoto metropolis does not mean it has no place in Islam. The study intends to assess the level and attitudes of Muslims of Sokoto State towards the pre-marital test. The paper specifically examines the extent to which the pre-marital medical test is observed in the metropolis and the societal perception of it from the Islamic perspective, bearing in mind that preserving human life is among the significant goals of Shari'ah in Islam. Hence, the paper discovers less patronage of pre-marital medical tests by people in the Sokoto metropolis, which many attributed to ignorance of their existence and poor perception of them. The paper underpins the importance of having these tests by would-be couples before marriage as well as the position of Islam on them so that people in the state can embrace them accordingly. The paper adopted a qualitative survey where interviews were conducted with individuals and the researchers purposively selected participants. In conclusion, the study highlighted some of the importance of pre-marital medical tests among the Muslim Ummah.